First steps in the development of an ovine proximal phalanx fracture and bone defect model: a study of animal welfare and bone healing - Nikolaisen, Nanett Kvist; Colding-Rasmussen, Thomas; Horstmann, Peter F.; Müller, Anna V.; Cerón, José Joaquín; Petersen, Michael Mørk; Tierp-Wong, Christian Nai En; Jacobsen, Stine (Frontiers in Veterinary Science, 2025)
There is a need for large-animal fracture models focusing on small tubular bones, as existing models typically involve major weight-bearing bones and often rely on restrictive suspension systems that raise significant animal welfare concerns. This study presents a novel in vivo sheep model targeting the proximal phalanx, designed to enable natural movement and social housing whilst supporting the investigation of fracture fixation and bone healing. Eleven skeletally mature Texel sheep were included; four underwent bilateral ostectomies with 3 mm or 6 mm defects, and seven received an osteotomy. A hoof block was used to offload the affected digit, enabling the sheep to move freely and to be housed in pairs. Bone healing was assessed using standardised radiographic scoring based on images obtained intraoperatively, at week 1 and 2, and hereafter every second week. Hard callus thickness was assessed at the end of the study period by a computed tomography-based method. Animal welfare was monitored through repeated clinical evaluations, two pain scoring systems (a validated sheep facial pain expression scale and a novel composite behavioural pain score), and biomarkers of inflammation, including serum amyloid A and haptoglobin. The ostectomy group showed frequent implant failure and limited healing, particularly in the 6 mm ostectomies, whilst the osteotomy group demonstrated relatively better stability and more consistent healing. Pain scores peaked shortly after surgery and again following withdrawal of analgesia but remained generally low. This study presents a novel, welfare-consciousness bilateral ovine proximal phalanx fracture model that challenges osteosynthesis stability. The integrated multimodal welfare assessment highlights the importance of objective pain and stress monitoring and advocates for the routine inclusion of quantitative welfare parameters alongside bone healing outcomes in translational orthopedic research.